Biodiversity of Aquatic Macrophytes in Suchindram Theroor Birds Sanctuary, Kanyakumari District, Tamil Nadu, India - Ramarajan, S.; Murugesan, A. G.; Saravana Gandhi, A. (Indian Forester, 2015)
A detailed survey of aquatic macrophytes in Suchindram Theroor Birds Sanctuary, Kanyakumari district of Tamil Nadu was made during the period of two year (January-2011 to December-2012). A total of 46 species belonging to 24 families and 35 genera were identified, of these 3 are pteridophytes and 43 angiosperms. Further, the aquatic macrophytes classified in morphological group viz., floating (12), submerged anchored and floating leaved anchored (7) and emergent anchored (20). In Suchindram Perennial water source of the "Sanctuary serves as an important gateway for the migratory waterfowl.